2017
DOI: 10.1002/jts.22185
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes Less is More: Establishing the Core Symptoms of PTSD

Abstract: Historically, the symptoms of posttraumatic stress disorder (PTSD) have garnered attention and controversy due to symptom overlap with other disorders. To improve diagnostic specificity, researchers have proposed to reformulate PTSD symptoms into a parsimonious set of core criteria. The core symptoms consisted of recurrent distressing dreams or flashbacks; internal or external avoidance; and hypervigilance or exaggerated startle. The purpose of this study was to examine a previously proposed set of "core" PTSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…However, negative alterations in cognitions and mood symptoms were expected to be elevated among our sample of SA survivors; thus, we were concerned that elevations in the negative alterations in cognitions and mood symptom cluster would yield a high rate of false positives if relying upon a total score cutoff‐based approach. By contrast, the algorithm‐based approach we utilized ensures that core PTSD symptoms (i.e., intrusion, avoidance, and hyperarousal; Walton et al, ) drive a probable diagnosis and, therefore, provides a more conservative estimated rate of SA‐related PTSD diagnoses within our sample (i.e., 27.2% [95% CI = 22.3–32.3%]). Nevertheless, for the curious reader, we note that, utilizing a PCL‐5‐SA cutoff score of >33 (based on the PCL‐5 cutoff score > 33; Weathers et al, ), 36.3% (95% CI = 31.6–40.9%; n = 140/386) of the sample screened positive for a probable SA‐related PTSD diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, negative alterations in cognitions and mood symptoms were expected to be elevated among our sample of SA survivors; thus, we were concerned that elevations in the negative alterations in cognitions and mood symptom cluster would yield a high rate of false positives if relying upon a total score cutoff‐based approach. By contrast, the algorithm‐based approach we utilized ensures that core PTSD symptoms (i.e., intrusion, avoidance, and hyperarousal; Walton et al, ) drive a probable diagnosis and, therefore, provides a more conservative estimated rate of SA‐related PTSD diagnoses within our sample (i.e., 27.2% [95% CI = 22.3–32.3%]). Nevertheless, for the curious reader, we note that, utilizing a PCL‐5‐SA cutoff score of >33 (based on the PCL‐5 cutoff score > 33; Weathers et al, ), 36.3% (95% CI = 31.6–40.9%; n = 140/386) of the sample screened positive for a probable SA‐related PTSD diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…risk of pre-injury presence of the outcomes as well as the risk of false positives when assessing PTSD in pain patients. Thus, we hope to encourage awareness of this potential issue and argue that future work on this should ensure endorsement of the A criterion and use clinically administered interviews or focus on the core symptoms of PTSD symptoms when using questionnaires [25,38,61], while neither, however, rule out the risk of false positives. Additionally, future research should report on statistical assumptions, control and discuss the role of confounding, and include effect sizes a long with confidence intervals.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…A few studies have directly compared these two diagnostic systems, yielding mixed results. According to a review by Brewin et al (2017), the DSM-5 tends to be associated with a higher PTSD prevalence than the ICD-11 (Hafstad, Thoresen, Wentzel-Larsen, Maercker, & Dyb, 2017;Hyland et al, 2016;O'Donnell et al, 2014;Tay, Rees, Chen, Kareth, & Silove, 2015;Walton et al, 2017;Wisco et al, 2016), with the exception of one study that showed a similar prevalence (Stein et al, 2014) and one that showed contradictory results (Danzi & La Greca, 2016). However, these previous studies had problems, as they used DSM-based measures to estimate ICD-11 symptoms and diagnostic algorithms.…”
Section: Introductionmentioning
confidence: 99%